Ответы и объяснения

2014-04-09T17:55:40+00:00
Разложим сперва числитель

x^3 - 6x^2 - 4x + 24 =
= x^2 (x-6) -4 (x-6) = 
= (x-6) (x^2-4) =
= (x-6) ( x-2) ( x+2)

 а теперь можно сократить

x^3 - 6x^2 - 4x + 24          (x-6) (x+2) (x-2)
------------------------------- = ----------------------------- =  x + 2
     (x-6) (x-2)                      (x-6) (x-2)



спасибо огромное выручила!;)
владей! :))
:)обязательно
Лучший Ответ!
2014-04-09T17:56:12+00:00
[(х^3 - 6x^2) - (4x - 24)] / (x -6)*(x - 2)=[x^2(x - 6) - 4(x - 6)] / (x -6)*(x - 2)=
=[(x - 6) * (x^2 - 4)] / (x -6)*(x - 2) = [(x - 6) * (x - 2) * (x + 2) ] /(x -6)*(x - 2) = 
= (x +2)